STUDI ISLAM DAN MASA DEPAN ISLAM: (Telaah Pemikiran Fazlur Rahman) - Robbani, Shofa (Universitas Nahdlatul Ulama Sunan Giri, 2019)
“This paper deals with Islamic studies and the future of Islam. Firstly, Fazlur Rahman considers that neo-modernists have acknowledged that Western civilization is the only alternative for the future of the world. He revealed a fact that modernity in the West, ethics, and law is able to develop as an independent discipline with secularism method. On the contrary, Islamic ethics was never developed as an independent discipline based on the systematic interpretation methodology of the Qur'an. Secondly, Rahman mentions the orthodoxy of Islamic thought on the obsolete methodology, such as qiya>s, must be reconstructed with a new methodological approach, such as maslahat, so that, the elasticity of Islamic law is able to provide solutions to all contemporary problems. In addition, Rahman highlighted the impact of the hegemony of Western civilization on the mindset and lifestyle of Muslim communities that can be seen in a variety of new situations that are full of complexity. Actually, he wants to create synergy between Muslim and non-Muslim intellectuals and can work together between them. In discussing the development of Islamic intellectualism, he said that something that was desired primarily was to understand the Qur'an with the historical background and new interpretations.”